Soapstone in northern Norway: research status, production evidence and quarry survey results - Wickler, Stephen (University Museum of Bergen, 2015)
Publisher's pdf. Complete book at http://hdl.handle.net/1956/10072 . Archaeological research on the production and use of soapstone artifacts in northern Norway remains limited in scope and the region has received marginal attention in the Norwegian soapstone literature. Archaeological documentation of soapstone quarry locations has been minimal, although the Geological Survey of Norway has systematically surveyed a majority of the soapstone exposures in the region and provided information on quarry activity. This paper begins by reviewing the current status of soapstone from archaeological contexts in northern Norway, including an overview of material in the Tromsø University Museum collection. Soapstone production evidence is reviewed and challenges associated with quarry documentation discussed. Results from recent collaborative geological and archaeological quarry surveys are presented and some sugg